Let $E \subset \mathbb{R}^n$ be a set of finite perimeter that satisfies $ \mathcal{L}^n (E) < \infty$. Assume that $E$ is symmetric with respect to the hyperplane $\{x_n = 0\}$. We know that there exists a sequence $(E_h)_h$ of bounded open sets having polyhedral boundary and that are symmetric with respect to the hyperplane $\{x_n = 0\}$ such that $$ E_h \to E \quad \text{as } h \to \infty \quad \text{and} \quad \lim_{h \to \infty}P(E_h) =P(E). $$ and $$\lim_{h \to \infty} P(E_h; F) = P(E; F) \text{ for all } F\subset \mathbb{R}^n \text{ that satisfies } P(E; \partial F )=0.$$ For all $h \in \mathbb{N}$ and $z \in \mathbb{R}^{n-1}$ let us set \begin{gather*} (E_h)_z := \{ t \in \mathbb{R} : (z,t ) \in E_h \}, \quad (E)_z := \{ t \in \mathbb{R} : (z,t ) \in E \} \\ m_h (z) := \mathcal{L}^1 ((E_h)_z) \text{ with }z \in \mathbb{R}^{n-1} , \quad G_h := \{ z \in \mathbb{R}^{n-1} : m_h (z) > 0 \} \\ m (z) := \mathcal{L}^1 (E_z) \text{ with }z \in \mathbb{R}^{n-1} , \quad G := \{ z \in \mathbb{R}^{n-1} : m(z) > 0 \} . \end{gather*} I have to prove that (up to a subsequence) $G_h \to G $ as $ h \to \infty$ (which means $\lim_{h \to \infty} \mathcal{L}^{n-1} (G_h \triangle G)= 0$).

My attempt: if we prove that $$\lim_{h \to \infty} \mathcal{L}^n ( G \setminus G_h) =0 \text{ and } \lim_{h \to \infty} \mathcal{L}^n ( G_h \setminus G) =0 $$ then I have finished.

By Fubini's Theorem (and using the fact that the vertical slices of these sets are intervals) it can be showed that \begin{equation*} \begin{split} \mathcal{L}^n( & E_h \triangle E) = \int_{\mathbb{R}^{n-1}} \mathcal{L}^1 \bigl( (E_h \triangle E)_z \bigr) \, dz = \int_{\mathbb{R}^{n-1}} \mathcal{L}^1 \bigl( {E_h}_z \triangle {E}_z \bigr) \, dz = \\ & = \int_{\mathbb{R}^{n-1}} \left| \mathcal{L}^1 ({E_h}_z) - \mathcal{L}^1 ({E}_z) \right| \, dz = \int_{\mathbb{R}^{n-1}} \left| m_h(z) - m(z) \right| \, dz. \end{split} \end{equation*} Therefore passing to the limit as $h \to \infty$ we get $$0 = \lim_{h \to \infty} \mathcal{L}^n ( {E_h} \triangle E) = \lim_{h \to \infty} \int_{\mathbb{R}^{n-1}} \left| m_h(z) - m(z) \right| \, dz. $$ Up to a subsequence, for a.e $z \in \mathbb{R}^{n-1}$, $m_h(z) \to m(z) $. This proves that $$ \lim_{h \to \infty} \mathcal{L}^n ( G \setminus G_h) =0,$$ Indeed for a.e. $z \in G$, since $m_h(z) \to m(z) $ and, by definition of $G$, $m(z) >0$ , we have that $m_h (z) > 0$ if $h$ is great enough, hence $z \in G_h$ if $h$ is great enough.

But we I don't know how to prove that $\lim_{h \to \infty} \mathcal{L}^n ( G_h \setminus G) =0$. The above argument can't be adapted to this case because I think there could exist $z \notin G$ (ie $m(z)=0$) such that $m_h (z) \to m(z)$ but $m_h(z) >0$ for all $h$ (thus $z \in G_h $ for all $h$). I've been trying for hours but I can't conclude!

Thank you very much for any advice!!

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Browse other questions tagged or ask your own question.